Desenvolvimento de material cerâmico para aplicação em processos de adsorção - Freitas, Vivian Loiane Carvalho de (2016)
Concern about the environment has grown a lot in recent years. In the region of Curitiba and Ponta Grossa there is a great industrial pole, being most of the industries of the area of the automobile and metallurgical area. The objective of this work was to analyze the behavior of the adsorbent immobilized in ceramic sponge in the process of adsorption of metals. In addition to the environmental issue, in the region where the study was carried out (Ponta Grossa and Curitiba) there are a large number of metallurgical and automotive industries that have effluents contaminated with toxic compounds and heavy metals. Thus, the present work of course conclusion aims to present a proposal that can reduce a stage of an environmental process, the separation of the adsorbent from the aqueous suspension by a sedimentador, producing a ceramic sponge with the immobilized adsorbent, for the removal of compounds that currently are in excess in the waters of the affected region of Minas Gerais and can also be applied in the treatment of industrial effluents in the region of Ponta Grossa and Curitiba.